Correction of amyotrophic lateral sclerosis related phenotypes in induced pluripotent stem cell-derived motor neurons carrying a hexanucleotide expansion mutation in C9orf72 by CRISPR/Cas9 genome editing using homology-directed repair. (5th June 2020) - Ababneh, Nidaa A; Scaber, Jakub; Flynn, Rowan; Douglas, Andrew; Barbagallo, Paola; Candalija, Ana; Turner, Martin R; Sims, David; Dafinca, Ruxandra; Cowley, Sally A; Talbot, Kevin
Abstract: The G4C2 hexanucleotide repeat expansion (HRE) in C9orf72 is the commonest cause of familial amyotrophic lateral sclerosis (ALS). A number of different methods have been used to generate isogenic control lines using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 and non-homologous end-joining by deleting the repeat region, with the risk of creating indels and genomic instability. In this study, we demonstrate complete correction of an induced pluripotent stem cell (iPSC) line derived from a C9orf72 -HRE positive ALS/frontotemporal dementia patient using CRISPR/Cas9 genome editing and homology-directed repair (HDR), resulting in replacement of the excised region with a donor template carrying the wild-type repeat size to maintain the genetic architecture of the locus. The isogenic correction of the C9orf72 HRE restored normal gene expression and methylation at the C9orf72 locus, reduced intron retention in the edited lines and abolished pathological phenotypes associated with the C9orf72 HRE expansion in iPSC-derived motor neurons (iPSMNs). RNA sequencing of the mutant line identified 2220 differentially expressed genes compared with its isogenic control. Enrichment analysis demonstrated an over-representation of ALS relevant pathways, including calcium ion dependent exocytosis, synaptic transport and the Kyoto Encyclopedia of Genes and Genomes ALS pathway, as well as new targets of potential relevance to ALS pathophysiology. Complete correction of the C9orf72 HRE in iPSMNs by CRISPR/Cas9-mediated HDR provides an ideal model to study the earliest effects of the hexanucleotide expansion on cellular homeostasis and the key pathways implicated in ALS pathophysiology.